ON ASPIRATIONS OF YOUTH FOR TECHNICAL FIELDS AND CRAFTS IN THE REGION OF SOUTH MORAVIA - FRIEDMANN, Zdeněk (Trends in education, 2009)
The paper presents several results of an investigation dealing with the situation in the field of professional aspirations at primary schools, secondary technical schools and vocational schools. The aim of the investigation was to find out the interest of pupils of primary schools (including pupils with special educational needs) in practical activities of technical type and the range, manner and level of cooperation of schools with other agents in the field of promotion of technical fields and crafts.
Keywords: Professional aspirations; unemployment; technical fields; drafte.